Gastroesophageal reflux disease: From pathophysiology to treatment - Herbella, Fernando A (Baishideng, 2010)
This review focuses on the pathophysiology of gastroesophageal reflux disease (GERD) and its implications for treatment. The role of the natural anti-reflux mechanism (lower esophageal sphincter, esophageal peristalsis, diaphragm, and trans-diaphragmatic pressure gradient), mucosal damage, type of refluxate, presence and size of hiatal hernia, Helicobacter pylori infection, and Barrett’s esophagus are reviewed. The conclusions drawn from this review are: (1) the pathophysiology of GERD is multifactorial; (2) because of the pathophysiology of the disease, surgical therapy for GERD is the most appropriate treatment; and (3) the genesis of esophageal adenocarcinoma is associated with GERD.